A knowledge-based system for determination of marginal value of building projects - Neap, HS; Celik, T (Pergamon-Elsevier Science Ltd, 2001)
Marginal value of a building is the subjective part of the value of the constructed facility and depends on how the decisions made by the contributing parties at different stages of the implementation of the project of a building. To increase the marginal value of a building, decisions made during the stages of a project need to be in close agreement with the value criteria of the decisions. Traditionally, during the implementation of a building project designers and clients make decisions with a little knowledge of the effects contributed by the decisions on the value the constructed facility. Knowledge of decisions to be made during the stages of a building project, value criteria of the decisions and their effects on the value of the constructed facility are important for successful project implementation. Therefore, determination of marginal value of a construction project lends itself to a knowledge-based application. This paper presents a knowledge-based system called COMVOB for the determination of the marginal value of a building project. To the user COMVOB presents criteria of decisions together with their importance weights at stages of a building project and with the input and confirmation of the details of the decisions it reports anticipated positive and negative marginal values. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: marginal value; value criteria; building projects; stages of construction; expert system